2014
DOI: 10.1142/s0192415x14500050
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Protects Cardiomyocytes Against Mitochondrial Oxidant Injury Associated with JNK Inhibition and Mitochondrial Akt Activation

Abstract: Baicalein, a flavonoid derived from Scutellaria baicalensis Georgi, possesses cardioprotection against oxidant injury by scavenging reactive oxygen species (ROS). Few studies investigate whether baicalein protection is mediated by attenuating mitochondrial ROS and modulating the prosurvival and proapoptotic signaling. Primary cultured chick cardiomyocytes were used to study the role of baicalein in mitochondrial superoxide [Formula: see text] generation and signaling of Akt and JNK. Cells were exposed to H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…Neurotoxin 6-hydroxydopamine (6-OHDA) induces initiation of mitochondria-regulated apoptotic cascade events in SH-SY5Y cells, which can be ameliorated by the administration of sulfuretin through inhibition of GSK-3β signaling and inactivation of NF-κB signaling [89]. Baicalein, isolated from Scutellaria baicalensis Georgi , increases mitochondrial phosphorylation of Akt-Thr308 and GSK-3β-Ser9, resulting in prevention of cytochrome c release in primary cultured chick cardiomyocytes [90]. …”
Section: Natural Compounds Regulate Mitochondrial Activity Through Gsmentioning
confidence: 99%
“…Neurotoxin 6-hydroxydopamine (6-OHDA) induces initiation of mitochondria-regulated apoptotic cascade events in SH-SY5Y cells, which can be ameliorated by the administration of sulfuretin through inhibition of GSK-3β signaling and inactivation of NF-κB signaling [89]. Baicalein, isolated from Scutellaria baicalensis Georgi , increases mitochondrial phosphorylation of Akt-Thr308 and GSK-3β-Ser9, resulting in prevention of cytochrome c release in primary cultured chick cardiomyocytes [90]. …”
Section: Natural Compounds Regulate Mitochondrial Activity Through Gsmentioning
confidence: 99%
“…Likewise, there was attenuation of markers of organ injury in EPO treated pigs in the HS-65 BV +VP series. The protective effects at the cell level reported by us [20] and others [32] in rats involve at the very least Akt activation (phosphorylation); a kinase that plays a key role in cell survival and other adaptive responses including mitochondrial bioenergetic function and enhanced myocardial contractility [33], [34]. In addition, plasma IL-10 was higher in pigs that received EPO at the end of blood reinfusion.…”
Section: Discussionmentioning
confidence: 89%
“…Phosphorylation of Akt and ERK1/2 was significantly increased. Our findings suggested that the underlying mechanisms of the protection of baicalein against AKI might be related to the inhibition of apoptosis, DNA laddering was also attenuated [14]. AKI is a severe complication of acute MI and cardiac surgery, and a treatment for preventing AKI might significantly improve clinical outcomes.…”
mentioning
confidence: 73%